Propriedades magnéticas de BiMn2O5 e Fe3O2BO3 - Fier, Igor (2018)
In this work, an exploration of the synthesis and magnetoelectric properties of single-crystals of BiMn2O5 and a systematic study of the magnetic properties of Fe3O2BO3 are presented. Despite the unlike composition, both materials share the same Pbam crystalline structure at room temperature and feature the coexistence of mixed valence sites of the transition metal ions. They also present a strong T^2 contribution of the specific heat at low temperatures. Magnetic frustration is also an important feature from where several of the remarkable physical properties of these materials arise. Macroscopic single-crystals of BiMn2O5 were synthesized by the flux method, whose quality was attested by the magnetic signature, just as found in literature. BiMn2O5 undergoes an antiferromagnetic transition around 40 K, which is correlated to the observation of magnetoelectric coupling. Such property was explored by means of high-sensitivity magnetic measurements with simultaneous application of electric field in one of the crystalline axes, revealing a shift of the magnetization vs. temperature data below 40 K. This is the first report of the direct measurement of magnetoelectric coupling on this material. The slight shift of the magnetization vs. magnetic field isotherms below ≈ 30 K suggests a trend for the incommensurate magnetic ordering that was observed in all RMn2O5, except for R = Bi. Fe3O2BO3 belongs to a family of materials that contain, in general, metallic ions located inside oxygen octahedra and boron ions in the center of oxygen triangles. For this reason, the crystalline structures in which boron coordinates in a triangular fashion tend to rearrange into substructures such as tapes, ladders or planes. Such arrangement gives these materials a strong anisotropy on the exchange interactions, from which several unconventional magnetic properties and low-dimensionality arise. A study of the magnetization at the paramagnetic phase under small applied magnetic fields allowed for the observation of a behavior like what Anderson and Hasegawa have suggested for the double-exchange interaction. A study of the angular dependence also allowed for the separation of the magnetic contribution of each sublattice to the net magnetization of the material. Specific heat measurements under magnetic field allowed for the correlation of each peak to its respective sublattice contribution.